Analysis of conflict resolution in physical education depending on a teacher's gender [Analýza řešení konfliktů v tělesné výchově v závislosti na pohlaví učitele] - Saša Vrbnjak; Jože Štihec; Mateja Videmšek (Palacky University, 2011)
BACKGROUND: Although many studies about conflict handling and resolution have so far been conducted, only a limited number of them have delved into the sphere of physical education. The specific nature of work with physical education in certain situations intensifies the occurrence of conflicts. The teacher as an expert in the educational process can, in such cases, provide a good example of how to handle a specific conflict. OBJECTIVE: The study aimed to gather information about differences in the resolving of conflict situations which arise during the physical education process between male and female physical education teachers in terms of which conflict resolution strategy they selected and how consistently they applied them. METHODS: For this purpose 158 physical education teachers from randomly selected Slovenian primary schools were surveyed (78 men and 80 women, aged 28-60 years) in April 2010. Teachers at selected schools volunteered to take part in the study and their participation was anonymous. A questionnaire (Bežek, 2000; Štihec, Bežek, Videmšek, & Karpljuk, 2004) with 17 questions was used. The frequencies of responses were calculated. The x2 test was applied at a 5% risk level (p ≤ 0.05) to verify whether there were any differences between male and female physical education teachers in terms of selecting a conflict resolution strategy. RESULTS: It was established that teachers use various approaches to resolving conflict situations. Most often they take an authoritarian approach ("insisting on one's own opinion"). Statistically significant differences were identified between the results of the male and female physical education teachers in some pedagogical situations in terms of choosing a conflict resolution strategy. CONCLUSIONS: The teachers mainly approach the resolving of conflict situations by "insisting on their own opinion". In the course of resolving a conflict, inconsistencies often occur but are mainly the consequence of the desire to ensure an efficient and the fastest possible elimination of the conflict behaviour. It was also established that in some cases the male physical education teachers differed from their female counterparts in terms of which conflict resolution strategies they selected. In further research some other factors, such as the teacher's age, cultural environment, the teacher's target orientation, the teacher's emotional intelligence andleadership styles could be analysed. [VÝCHODISKA: V minulosti bylo provedeno mnoho studií zabývajících se řešením konﬂiktů, avšak pouze malé množství z nich se blíže zabývalo tělesnou výchovou. Speciﬁcká povaha práce v rámci tělesné výchovy v určitých situacích zvyšuje míru výskytu konﬂiktů. Učitel jako odborník v oblasti výchovného procesu v takových případech může být dobrým příkladem toho, jak zvládat daný konﬂikt. CÍLE: Studie byla zaměřena na shromažďování informací o rozdílných přístupech učitelů a učitelek tělesné výchovy při řešení konﬂiktních situací, jež se vyskytují v hodinách tělesné výchovy, se zaměřením na výběr strategií řešení konﬂiktů a jejich důslednou aplikaci. METODIKA: K tomu účelu byl v dubnu roku 2010 proveden průzkum u 158 učitelů tělesné výchovy z náhodně vybraných slovinských základních škol (z toho 78 mužů a 80 žen ve věku 28-60 let). Učitelé z vybraných škol se studie zúčastnili dobrovolně a jejich účast byla anonymní. Byl použit dotazník (Bežek, 2000; Štihec, Bežek, Videmšek, & Karpljuk, 2004) se 17 otázkami. Byla spočtena četnost odpovědí. K prokázání toho, zda mezi učiteli a učitelkami tělesné výchovy existují rozdíly, pokud jde o výběr strategií řešení konﬂiktů, byl použit test x2 při míře rizika 5 % (p ≤ 0,05). VÝSLEDKY: Bylo prokázáno, že učitelé používají různé metody řešení konfliktních situací. Nejčastěji používají autoritativní přístup ("trvání na vlastním názoru"). Statisticky významné rozdíly byly zjištěny mezi výsledky učitelů a učitelek tělesné výchovy v některých pedagogických situacích, pokud jde o výběr strategií řešení konﬂiktů. ZÁVĚRY: Učitelé k řešení konfliktních situací přistupují především tak, že "trvají na svém názoru". Při řešení konfliktu se často vyskytuje nedůslednost, která je však ve velké míře důsledkem touhy nalézt efektivní a co nejrychlejší řešení konfliktního chování. Bylo také prokázáno, že v některých případech se učitelé tělesné výchovy odlišovali od svých ženských protějšků v tom, jaké strategie řešení konfliktů zvolili. V dalším výzkumu je možné se zaměřit na analýzu některých jiných faktorů, jako je například věk učitele, kulturní prostředí, cílová orientace učitele, jeho emoční inteligence a styl vedení.]